Effect of spacing and micronutrients on yield of bitter gourd (Momordica charantia) grown under protected structures - SINGH, ABHAY VIKRAM; SINGH, AWANI KUMAR; JAT, GOGRAJ SINGH; BEHERA, TUSAR KANTI (The Indian Journal of Agricultural Sciences, 2022)
Proper plant spacing and foliar application of micronutrients is necessary for higher yield and quality. Theexperiment was conducted to determine the effect of spacing and micronutrients on fruit yield of bitter gourdgrown under protected structures (nethouse and polyhouse). The variety Pusa Rasdar (27.06 days) showed superiorperformance over Selection 32 (30.03 days) for opening of first female flower under net house. The wider spacing(30 cm × 50 cm) enhanced early female flower (28.29 days) compared to closer spacing (under nethouse). The PusaRasdar was superior for node number of first female flower (11.25 nodes) followed by Selection 32 (13.28 nodes)(under nethouse). The wider spacing (30 cm × 50 cm) had a significant effect on first node of female flower appearance(12.37 and 11.87 nodes) under polyhouse and net house. The maximum fruit weight was in Pusa Rasdar (206.89g) (under nethouse). The application of boron @0.2% and calcium @0.6% enhanced the number of fruits per plant(11.00 and 10.80) (under net house). The wider spacing (30 cm × 50 cm) also produced the highest number of fruitsper plant (11.37) in Pusa Rasdar (under net house) condition. The maximum fruit yield per plant was recorded in PusaRasdar (2122.70 g) compared to Selection 32 (1646.61 g) (under net house). The wider spacing (30 cm × 50 cm) alsoproduced maximum fruit yield (2137.25 g) in Pusa Rasdar (under net house). Therefore, higher yield of bitter gourdcould be obtained under net house with broader spacing (30 cm × 50 cm) along with proper doses of micronutrients(0.2% boron and 0.6% calcium).